An Exploration of the Factors Hindering Students’ Lesson Comprehension in EMI Classes - Tran, Ngoc Tien; Tran, Thi Bao Trinh; Bien, Thi Thanh Mai (International Journal of Language and Literary Studies, 2020)
The implementation of English as a medium of instruction (EMI) has been found to bring numerous benefits to its learners. There has been a rising trend in introducing EMI at higher education institutions worldwide. However, challenges are ubiquitous and there is still prevalent hesitation in integrating content and language in many institutions. This study aimed to explore factors hindering students’ level of lesson comprehension in EMI classes through a mixed-method study carried out on 233 participants at Hoa Sen University, Vietnam. The findings showed that variables hampering students from lesson understanding were mainly associated with instructors’ teaching methods and students’ and instructors’ language competences. Results from standard multiple regression indicated that vocabulary range, writing skills and teaching methods were found to have significant contribution to the prediction of the level of lesson comprehension of the students. The findings of the study could be a considerable reference source for universities aiming at implementing EMI programmes.